Effects of Women’s Participation in Household Decision Making on Skilled Birth Attendants Supervised Delivery in Bangladesh - Md Badsha Alam; Shimlin Jahan Khanam; Md Awal Kabir; Atika Rahman Chowdhury; Tahir Ahmed Hassen; Susmita Das; Md Nuruzzaman Khan (Health Services Insights)
Background: While the importance of women’s participation in household decision making in enhancing access to healthcare services is widely acknowledged, limited evidence exists on the link between women’s participation in household decision making and skilled birth attendants (SBA) supervised delivery. This study aims to fill this gap by examining the effects of women’s participation in household decision making on SBA supervised delivery in Bangladesh. Methods: Data of 3607 mothers who had given birth within 2 years of the survey date were extracted from the 2022 Bangladesh Demographic and Health Survey (BDHS) and analyzed. The outcome variable considered was SBA supervised delivery, and the primary explanatory variable was a composite index of women’s participation in household decision making generated from their responses regarding decision-making on own healthcare, large household purchases, and visits to their family or relatives. Multi-level mixed-effects logistic regression was used to explore the effects of women’s participation in household decision making on SBA supervised delivery, adjusted for potential confounders. Results: The reported prevalence of SBA supervised delivery was 70%. Women lacking participation power and moderately empowerment in household decision-making were 15% (aOR= 0.85, 95% CI: 0.66-1.08) and 20% less likely to had SBA supervised delivery (aOR = 0.80, 95% CI: 0.64-0.99) compared to those with high participation power, respectively. This association remained consistent across all 3 empowerment domains, with lower likelihoods of SBA supervised delivery among women lacking empowerment. Conclusion: The findings of this research affirm the positive effects of women’s participation in household decision making on SBA supervised delivery in Bangladesh. Recommendations include increasing women’s empowerment in household decision making and raising awareness and education about the importance of SBA supervised delivery.